On Generalized Tribonacci Sedenions - Soykan, Yüksel; Okumuş, İnci; Taşdemir, Erkan (Sarajevo Journal of Mathematics, 2022)
The sedenions form a 16-dimensional Cayley-Dickson algebra. In this work, we introduce the generalized Tribonacci sedenion and present some properties of this sedenion.